2017
DOI: 10.1002/cre2.94
|View full text |Cite
|
Sign up to set email alerts
|

Genotypic characterization and comparison of Streptococcus mutans in American Indian and Southeast Iowa children

Abstract: Early childhood caries is a complex health care issue that has a multifactorial etiology. One aspect of this etiology is the colonization and propagation of acidogenic bacteria at an early age. There have been several bacterial species associated with caries but 1 common species is Streptococcus mutans. Here, we describe genotypic diversity and commonality of Streptococcus mutans recovered from children representing 2 groups with similar socioeconomic demographics: a Northern Plains American Indian Tribe and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 69 publications
0
5
0
Order By: Relevance
“…The development of the oral microbiome in children is influenced by both maternal and environmental sources (11,12). While other aspects of our overarching study have examined environmental influences that may play a role in the rampant caries observed in this population (4), the focus of microbiological reporting to date has been on genotypic diversity and maternal transmission of S. mutans (16,17). Much research on the influence of the mutans streptococci on caries progression has indicated that the presence of S. mutans and S. sobrinus together results in greater disease risk than S. mutans alone (8,24,27,(41)(42)(43).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The development of the oral microbiome in children is influenced by both maternal and environmental sources (11,12). While other aspects of our overarching study have examined environmental influences that may play a role in the rampant caries observed in this population (4), the focus of microbiological reporting to date has been on genotypic diversity and maternal transmission of S. mutans (16,17). Much research on the influence of the mutans streptococci on caries progression has indicated that the presence of S. mutans and S. sobrinus together results in greater disease risk than S. mutans alone (8,24,27,(41)(42)(43).…”
Section: Discussionmentioning
confidence: 99%
“…After observing unexpectedly high levels of S. sobrinus in the population (71% of research participants have S. sobrinus present), we expanded the scope of work to include isolation and genotypic analyses of both mutans streptococci (MS) species. We have previously reported on initial acquisition and genotypic diversity of S. mutans in this study population (16,17). The focus of this manuscript is 2-fold: (1) analyses of the presence of S. mutans, S. sobrinus, and lactobacilli in children from this cohort, including exploration of colonization patterns for the three bacterial species of interest;…”
Section: Introductionmentioning
confidence: 99%
“…Napimoga et al [8] in their study demonstrated that more genotypes were found in caries-active subjects than those caries-free subjects. On the other hand, Kreulen et al and other researchers in their study showed a negative correlation between caries activity and the genotypic diversity [9][10][11][12]. The possible association between the biodiversity of S mutans and caries activity among the Indian population deserves attention, as there is paucity in the literature.…”
Section: Introductionmentioning
confidence: 93%
“…Severe early childhood caries can disproportionately affect American Indian (USA) and First Nation (Canada) children [ 149 , 150 ]. The caries-associated microbiota includes a very high prevalence and high levels of S. mutans [ 151 ], with differences in the genetic diversity of S. mutans compared with other children in the local area [ 152 ]. To further investigate the microbiome of aggressive caries, advanced carious lesions observed in Romanian adolescents who had very limited dental care were compared with a Swedish population with lower caries experience [ 153 ].…”
Section: Caries Microbiome At Different Lesion Sitesmentioning
confidence: 99%